Comparison of diffusion-weighted imaging and enhanced T1-weighted sequencing in patients with multiple sclerosis. Issue 4 (August 2017) - Abolhasani Foroughi, Amin; Salahi, Roohollah; Nikseresht, Alireza; Heidari, Hora; Nazeri, Masoume; Khorsand, Ali
Introduction: The purpose of this study was to assess whether demographic, brain anatomical regions and contrast enhancement show differences in multiple sclerosis (MS) patients with increased diffusion lesions (ID group) compared with diffusion restriction (DR group). Method: MRI protocol comprised T1- and T2-weighted sequences with and without gadolinium (Gd), and sagittal three-dimensional FLAIR sequence, DWI and ADC maps were prospectively performed in 126 MS patients from January to December 2015. The investigation was conducted to evaluate differences in demographic, cord and brain regional, technical, and positive or negative Gd contrast imaging parameters in two groups of ID and DR. Statistical analysis was performed by using SPSS. Results: A total of 9.6% of patients showed DR. In the DR group, 66.6% of the patients showed contrast enhancement of plaques, whereas 29.2% of the IR group showed enhancement of plaques. The most prevalent group was non-enhanced plaques in the ID group, followed by Gd-enhanced plaques in the ID group. Patients in the ID group (90.4%) were significantly more than in the DR group (9.6%). Out of the 40 patients with Gd-enhanced plaques, 80.5% was from the ID group and 19.5% from the DR group. Conclusion: MRI of the brain, unlike of the cord, with Gd demonstrates significant difference in enhancement between the two groups ( p < 0.05). No significant difference was seen in demographic, cord and brain regional, and technical parameters, EDSS, disease duration, and attack rate as well as demographic and regional parameters between the ID and decrease diffusion groups ( p > 0.05).